The Influence of Muhadharah as Extracurricular Activitiy on Students’ Speaking Ability - Alqadri, Aqbar; Patahuddin, Patahuddin; Ziska, Ika Yanti (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
Muhadhoroh is a human activity in discussing a problem by giving a speech or discussion which is attended by many people. In this case, muhadhoroh is one of an training activity that focused on the way of students speak. Therefore, The objective of this study was to find out how is the influence of muhadharoh as extracurricular activities on students' speaking ability in PPM Rahmatul Asri. This study used qualitative research. The participants in the study consisted of 14 eighth grade students at PPM Rahmatul Asri junior high school. Researchers conducted interviews to obtain data from participants. The results of this study indicate that extracurricular muhadharah is a good school extracurricular activity that can affect students' speaking ability based on the results of interviews, the results of interviews show that muhadharah extracurricular activities greatly affect students' speaking ability in English. As for the supporting things contained in muhadharah activities such as debriefing in speech procedures, increasing students' vocabulary, learning how to make facial expressions or body gestures and also being able to directly train students mentally to speak in public. The results of the interview also show that there are deficiencies in extracurricular activities such as muhadharah when the activity is not appropriate because it is carried out at night so that it takes students' rest time and makes some students tired and sleepy, there are also students who say that in this activity there are penalties if students violate.